Annual Survey of Jails: Jurisdiction-Level Data, 2002 ([Verlag nicht ermittelbar], 2006)
This collection provides annual data on jail populations across the nation and examines the "spillover" on local jails resulting from the dramatic growth in federal and state prison populations. These data are used to track growth in the number of jails and their capacities nationally, changes in the demographics of the jail population (including sex, race, and adult or juvenile status), supervision status of persons held, prevalence of crowding issues, and a count of non-United States citizens within the jail population.